PENERAPAN PENYAJIAN LAPORAN KEUANGAN BERDASARKAN PERATURAN PEMERINTAH NOMOR 71 TAHUN 2010 PADA BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN BOYOLALI - Rahmasari, Noviyati; Hegy Suryana, Alean Kistiani; Triatmaja, Nur Asih (EKOBIS, 2023)
The purpose of this research is to find out the implementation of the presentation of financial reports based on Government Regulation Number 71 of 2010. The method used in this research is descriptive with a qualitative approach. Data obtained through observation, interviews and documentation. The processed data comes from the financial reports of the Boyolali Regency National Unity and Political Unity Agency (BAKESBANGPOL) for 2021-2022. The results of this study show that the implementation of PP No. 71 of 2010 is in accordance with BAKESBANGPOL Boyoali Regency and implemented starting in 2015, there are only 5 components such as Budget Realization Reports, Operational Reports, Changes in Equity Reports, Balance Sheets and Notes to Financial Statements. Bakesbangpol does not make a cash flow report but makes a general cash book, for OPD cash flow, of course, zero. And don't make a report on changes to the balance of the budget excess, because when there is a balance it is submitted to the City Government, as the Government which has authority over the balance. Thus, it is the City/Regency Government that makes the cash flow reports and reports on changes in the balanceof the excess budget. Financial reports used. Financial reports are used to measure performance achievements, evaluation materials and decision making of a Regional Government Organization (OPD) in this case at BAKESBANGPOL. There are several presentation obstacles such as the lack of human resources (HR) who have not fully mastered their field and the lack of socialization regarding this matter and there are 3 factors that influence the implementation of PP No. 71 of 2010.